Peran Guru dalam Pembentukan Karakter Peserta Didik: Studi Kasus di SMKN SPP Merangin - Rita Rahmatillah; Nela Silvia; Siti Annisa; Yusrizal Yusrizal (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
This study aims to analyze the role of teachers in shaping students’ character at SMKN PP Merangin. The research employed a qualitative approach with a case study design. The research participants consisted of teachers, students, and the school principal selected through purposive sampling. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results show that teachers play a strategic role in character formation through several key roles, namely as role models, mentors, educators, supervisors, and motivators. These roles are implemented through disciplinary habituation such as punctuality and adherence to school rules, the integration of character values such as responsibility and cooperation in learning activities and vocational practices, and the provision of positive reinforcement and educational corrective feedback toward students’ behavior. In addition, teachers’ exemplary attitudes, discipline, and communication serve as important factors that encourage students to imitate positive behaviors in daily school life. These findings indicate that students’ character formation occurs through continuous pedagogical interactions between teachers and students within the school environment.